German boy : a refugee's story - Samuel, Wolfgang W. E. (Willie Morris books in memoir and biography., 2000)
A refugee child's witness to Nazi defeat, Soviet occupation, and his family's debacle in war What was the experience of war for a child in bombed and ravaged Germany? In this memoir the voice of innocence is heard. "This is great stuff," exclaims Stephen E. Ambrose. "I love this book." In this gripping account a boy and his mother are wrenched from their tranquil lives to forge a path through the storm of war and the rubble of its aftermath. In the past there has been a spectrum of books and films that share other German World War II experiences. However, told from the pers.